Reluctance Reasons for Grade 10th Students to choose physics from their point of view in Sultanate of Oman - Al-Kalbani, Said Mohammed; Al-Adili, Abdulaslam (Journal of Educational and Psychological Sciences, 2020)
The aim of study was to reveal the reasons for the reluctance of students in the tenth grade to choose physics in the Sultanate of Oman, from the point of view of the students themselves post-basic education schools. The study used the descriptive analytical approach. The sample of the study consisted of 367 students and it was selected in a stratified random method. A questionnaire was developed to answer the research questions. The results of the study showed that the reasons related to the subjects of physics and to the science teachers have a high level of influence in the reluctance of students to choose physics.  The results showed statistically significant differences at the level of significance (α = 0.05) in the axis of the reasons related to physics subjects in favor of female students and differences in the axis of the reasons related to the students themselves. Consequently, the researcher recommended analyzing the subjects and the curricula of physics by specialists in the fields of education and science and redesigns them in accordance with the scientific development and levels of students according to international standards. The researcher directed school professionals to intensify guidance for 10th grade students towards the requirements of the labor market associated with physics.
Keywords: reluctance; physics